Affective domain and mathematics achievement of Colombian students under multiple correspondence analysis - Prada Núñez, Raúl; Rabelo Procopio, Marcos V.; Fernández-Cézar, Raquel; Solano-Pinto, Natalia (Frontiers in Education, 2024)
The literature review indicates that age is a variable related to the students' affect toward mathematics in such a way that the older they are, the less affection they feel for mathematics. In the case of the Department of Norte de Santander, the administration is going to carry out an educational program for 2050, whose aim is to make this region a science, technology, engineering, arts, mathematics (STEAM) territory, for which it is necessary for students, regardless of the grade, to reach optimum levels in the management of mathematical competencies. Therefore, having a picture of the department's situation in this respect is relevant. To this end, this research aims to apply a quantitative and descriptive methodology on the affective domain and achievement in mathematics to determine whether these vary with the students' grade level. A non-probabilistic sample of 2,729 students from fourth to eleventh grades (9 to 18 years old) from 13 educational institutions in a region of northwestern Colombia was used. The instrument used characterized the affective domain toward mathematics (attitudes, beliefs, and emotions) and math achievement, taking grade as the independent variable. A multiple correspondence analysis (MCA) was carried out to depict the affective domain toward mathematics in relation to grade level, considering whether students like the subject and achievement as factors. The results allow us to identify that for beliefs and attitudes, the favorable values are located toward the positive axis of the abscissae, contrary to what is found for emotions. It is noteworthy that students in the lowest grade, fourth grade, show positive beliefs, attitudes, and emotions toward mathematics as well as high achievement, while those in the last grade, eleventh grade, show low values of the three components, besides low performance. This situation is worrying as mathematical knowledge is integral to everyday life and is necessary for citizens in the development of any profession. For this reason, relevant administration should take this into consideration when developing the STEAM program in order to promote an improvement in mathematical performance by supporting students in developing their affect toward mathematics.